2004
DOI: 10.1016/j.scitotenv.2004.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of organic compounds and ecotoxicological assessment of sewage treatment plants (STP) effluents

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
27

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 38 publications
0
29
0
27
Order By: Relevance
“…These compounds enter the aquatic environment via wastewater treatment plants, agricultural facilities, and farm runoff (Culp et al 2000;Folmar et al 1996;Wallin et al 2002;Wildhaber et al 2000). These products are the source of both natural and synthetic substances including, but not limited to, polychlorinated biphenyls, phthalates, pesticides, heavy metals, alkylphenols, polycyclic aromatic hydrocarbons, 17β-estradiol, 17α-ethinylestradiol, and bisphenol A (Aguayo et al 2004;Björkblom et al 2009;Iwanowicz et al 2009;Nakada et al 2004;Pait and Nelson 2002). The impact of these exposures on Gulf sturgeon is unknown, but other species of fish are affected in rivers and streams.…”
Section: Marine Pollution and Environmental Contaminationmentioning
confidence: 99%
“…These compounds enter the aquatic environment via wastewater treatment plants, agricultural facilities, and farm runoff (Culp et al 2000;Folmar et al 1996;Wallin et al 2002;Wildhaber et al 2000). These products are the source of both natural and synthetic substances including, but not limited to, polychlorinated biphenyls, phthalates, pesticides, heavy metals, alkylphenols, polycyclic aromatic hydrocarbons, 17β-estradiol, 17α-ethinylestradiol, and bisphenol A (Aguayo et al 2004;Björkblom et al 2009;Iwanowicz et al 2009;Nakada et al 2004;Pait and Nelson 2002). The impact of these exposures on Gulf sturgeon is unknown, but other species of fish are affected in rivers and streams.…”
Section: Marine Pollution and Environmental Contaminationmentioning
confidence: 99%
“…Each extract was evaporated to 50 l with a gentle stream of nitrogen for derivatization. For in vitro assay, the treatments of samples were similar to that for chemical analysis without spiking with E 2 -d 4 . Moreover, each extract for in vitro assay was evaporated to dryness and transferred into 50 l of DMSO.…”
Section: Sampling and Pretreatmentmentioning
confidence: 99%
“…In recent years, many studies have focused on the estrogenic compounds in the influents and effluents from STPs by biological and chemical analysis [3,4,7,8,12,13] as well as on the estimation of the possible effects on health and reproduction of freshwater fish [3,11]. The reported ranges of steroidal compounds were 1 to 10 ng/L for E 2 , 5 to 20 ng/L for E 1 , and less than 0.1 to 1 ng/L for EE 2 in effluents [7,8,17,18].…”
Section: Seasonal Variations Of Estrogenic Compounds In Influent and mentioning
confidence: 99%
“…However, the secondary effluent has been found to cause some adverse aqua-ecological effects. Aguayo et al (2004) found that the effluent from 7 investigated STPs all showed toxic effects to Daphnia magna, while some samples showed estrogenicity and teratogenicity. Dizer et al (2002) reported that samples taken from a river accepting the secondary effluent caused genotoxic responses in the umu assay.…”
Section: Introductionmentioning
confidence: 98%